Awaiting for epistemic injustice: comparative analysis of theories of preventive anticipatory injustices - Sidorova Стефанія (Actual Problems of Mind, 2023)
The author demonstrates that Miranda Fricker’s idea of pre-emptive testimonial injustice may be expanded and deepened, but is in itself insufficient to cover the entire spectrum of preventive injustices. Drawing on Kristy Dotson’s theory of testimonial smothering and quieting, she shows the successful operation of an alternative, narrow theory of preventive injustice, which, nevertheless, cannot be expanded without substantial modification. As an example of an extended theory aimed at such cases, the author analyses Ji Young Lee’s theory of anticipatory epistemic injustice and reveals its flaws. Comparing the three mentioned theories, the author formulates the requirements that a fuller theory of preventive-anticipatory injustices must meet and foresees possible development directions. “Neo-nazis heuristic” is introduced as a method for a quick evaluation of future theoretical candidates.